Faktor-faktor yang berpengaruh terhadap pendapatan pedagang perempuan berjualan sayur-sayuran (Pasar Angso Duo Kota Jambi) - Foky Weldo; Heriberta Heriberta; Hardiani Hardiani (Konsentrasi Ekonomi Sumberdaya Alam dan Manusia, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2021)
Initially the general reason for working women was to help the family economy. This study aims to: 1) To analyze the social and economic characteristics of female traders selling vegetables at the Angso Duo market in Jambi City. 2) To analyze the contribution of income of women traders selling vegetables to family income. 3) To analyze the effect of operational capital, age, education level, number of dependents, hours of work and business locations of women traders selling vegetables in the Angso Duo market in Jambi City. The research analysis tool uses multiple linear regression analysis tools. Based on social characteristics, the average age of business traders is around 41-50 years, for the average education level of female traders is junior high school graduates and the average number of dependents owned by respondents in this study is 2-3 people. While the economic characteristics of women traders show that the average working hours of women traders is 7-8 hours, the average traders selling in strategic places, the average operating capital of women traders is Rp. 600,000 per month and the average income of vegetable traders is below Rp. 5,000,000. Based on the results of multiple linear regression, it can be concluded that partially only operating capital and location variables have a significant effect on the income of female traders.